Gender Based Inequalities in Labor Market Outcomes - Pecháčková, Monika; Klosová, Anna, 1942-; de Lara Resende, José Guilherme; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
This thesis focuses on gender based differences in occupational allocation in Central-European countries, i.e. in Croatia, the Czech Republic, Hungary, Poland, Slovakia and Slovenia. The main goal is to find out how much of the gender differences is related to women being equipped with higher/lower human capital in comparison to men. This thesis uses data from 2010 Life in Transition Survey provided by the European Bank for Reconstruction and Development. Focus will be placed on white/blue collar occupations split. For the empirical analysis an extension of the Oaxaca-Blinder decomposition for binary dependent variable model provided by Fairlie (2005) will be used.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; economics of globalisation and european integration [obor dipl. práce]